Precision medicine in hypertension: are we there? / Hoh-Boon-Peng, Fananta Ibrahim and Nur Hasnah Maamor - Peng, Hoh-Boon; Ibrahim, Fananta; Maamor, Nur Hasnah (Faculty of Medicine, 2024)
Hypertension (HTN), clinically defined as systolic blood pressure (SBP) > 140 mmHg, or diastolic blood pressure (DBP) > 90 mmHg, or both affects approximately 1.28 billion people aged between 30 and 79 years globally [1, 2]. The overall global prevalence of hypertension in 2000 was estimated at 26.4% [3]. In the 2015 estimates, however, the average prevalence had increased to 32.3% in low- and middle-income countries, with prevalence estimates of 39.1% in the Latin American and Caribbean regions [4]. Interestingly, the prevalence of hypertension was also reportedly the highest in populations from the upper middle-income countries (37.8%) and lowest in populations from low-income countries (23.1%) [4]. In addition, prevalence estimates were higher in those aged 65 years and above compared with that in those below 65 years of age. No significant gender-difference in hypertension prevalence was noted, but persons with no formal education (49.0%), or who were overweight/obese (46.4%), and urban settlers (32.7%) were more likely to be hypertensive compared with those who were educated, normal weight, and living in rural areas [4]. In Malaysia, the 2023 National Health and Morbidity Survey (NHMS, 2023) revealed that approximately one in three adults in Malaysia have hypertension [5].